Resection Status Does Not Impact Recurrence in Well-Differentiated Liposarcoma of the Extremity. Issue 11 (November 2021) - Olson, Chelsea R.; Suarez-Kelly, Lorena P.; Ethun, Cecilia G.; Shelby, Rita D.; Yu, Peter Y.; Hughes, Tasha M.; Palettas, Marilly; Tran, Thuy B.; Poultsides, George; Tseng, Jennifer; Roggin, Kevin K.; Chouliaras, Konstantinos; et al.
Background: Well-differentiated liposarcoma (WDLPS) is a low-grade soft tissue sarcoma with a propensity for local recurrence. The necessity of obtaining microscopically free surgical margins (R0) to minimize local recurrence is not clear. This study evaluates recurrence-free survival (RFS) of extremity WDLPS in relation to resection margin status. Methods: A retrospective review of adult patients with primary extremity WDLPS at seven US institutions from 2000 to 2016 was performed. Patients with recurrent tumors or incomplete resection (R2) were excluded. Clinicopathologic factors were analyzed to assess impact on local RFS. Results: 97 patients with primary extremity WDLPS were identified. The majority of patients had deep, lower extremity tumors. Mean tumor size was 18.2±8.9cm. Patients were treated with either radical (76.3%) or excisional (23.7%) resections; 64% had R0 and 36% had microscopically positive (R1) resection margins. Ten patients received radiation therapy with no difference in receipt of radiation between R0 vs R1 groups. Thirteen patients (13%) developed a local recurrence with no difference in RFS between R0 vs R1 resection. Five-year RFS was 59.5% for R0 vs 85.2% for R1. Only one patient died of disease after developing dedifferentiation and distant metastasis despite originally having an R0 resection. Discussion: In this large multi-institutional study of surgical resection of extremity WDLPS, microscopically positive margins were not associated with an increased risk of recurrence. Positive microscopic margin resection for extremity WDLPS may yield similar rates of local control while avoiding a radical approach to obtain microscopically negative margins.